INICIB: Driving scientific research in the faculty of human medicine of the Ricardo Palma University - De La Cruz Vargas, Jhony A. (2018)
Biomedical research is fundamental for the development and advancement of the people and society as a whole. There is a need and responsibility of universities to produce new knowledge and tools for the resolution of current health problems, as well as the need for a better distribution of health benefits resulting from research, since a large number of people in the least developed countries have little or no benefit with the tools created in the richest countries to meet the health needs of populations in those same countries 1.The Institute of Research in Biomedical Sciences: INICIB of the Universidad Ricardo Palma opened a new stage of scientific research in the Faculty of Human Medicine in 2017, deepening the formative research and promoting scientific research. A fundamental step was taken when winning and obtain financing from CONCYTEC-CIENCIA ACTIVA, to carry out the research project entitled: MOLECULAR PANELS FOR CANCER OF PULMON, MELANOMA AND COLON. This project is the result of the strategic collaboration established between Universidad Ricardo Palma with  ESSALUD-IETSI, on the one hand, and with the productive sector represented by the ARC-PER organization on the other.• The relevance of this research project, for the period 2018-2019, is multiple:• Addresses a priority issue in public health in Peru and in the world: Cancer.• Incorporates advanced molecular and genomic technology platforms at an international level.• It is an original work that explores the molecular profile of cancer and the genomic profile of thePeruvian population with these three types of cancers.• Establishes collaborations with prestigious Research Centers in Europe and the United States.• Generates Technology Transfer and Research Methodologies for the participating centers.• Integrates the participation of human resources in health research training, both undergraduateand postgraduate.• Produces the participation of multidisciplinary research teams, linking university teachers,government institutions, the productive sector and international centers.• The most important: It will provide knowledge and innovation for the diagnosis in Peru of cancerpatients, as well as their potential prognostic and therapeutic applications.  DOI: 10.25176/RFMH.v18.n2.1278